Dalsza cześć wyrażeń algebraicznych
14. -(¾x+2y)-(-½x-y-2) =
15. (-⅗xy+2y)-(-0,6xy+2⅖x) =
16. 1-[-5x+(3+4x)] =
17. -4+[-2a-(-3a+2b-4)] =
18.-1,8x-[-(x+1)+(0,8x-1)] =
19. -(¾x+2)-[-(5+0,5x)+3] =
20. ⅘a+[-(0,2a-1)-b]-(⅖b-a) =
21. [-⅔x+(-⅗y-⅚x) =
22. [0,8a-(-1,2a+0,4b)]-(2a-0,3b)=0,1b =
23.-[-2p-(⅝p+0,4)]-[2,5p+(⅛p-1,6)] =
24. ½(2a-4b)+⅓(3a+9b) =
25.¾(a-b)-⅛(a-+b) =

1

Odpowiedzi

2010-02-17T15:45:53+01:00
15. (-3/4xy+2y) - (-0.6xy+2i2/5x)=
= 3/5xy+2y-0.6xy+2i2/5=
=3/5xy+2i2/5x+2y-0.6xy=
= 3/5xy-6/10xy+2i2/5x+2y=
= 6/10xy-6/10xy+2i2/5x+2y=
= 2i2/5+2y

16. 1-[-5x+(3+4x)]=
= 1-[-5x+3+4x]=
= 1-5x+3+4x]=
= 4-1x

17. -4+[-2a-(-3a+2b-4)]=
=-4+[-2a-(3a-2b+4)]=
=-4+[-2a-3a+2b-4]=
=-4-2a-3a+2b-4=
=-8-5a+2b

25. 3/4(a-b)-1/8(a+b)=
=3/4a-3/4b-1/8a-18/b=
=3/4a-1/8a-3/4b-1/8b=
=6/8a-1/8a-6/8b-1/8b=
=5/8a-5/8b

24. 1/2(2a-4b)+1/3(3a+9b)=
=1/2(2/1a-4/1b)+1/3(3/1a+9/1b)=
=1a-2b+1a+3b=
=2a+1b